MAKNA KAJIAN AKUNTANSI LINGKUNGAN PADA PT SEMEN BOSOWA MAROS: KAJIAN AKUNTANSI LINGKUNGAN (Studi Pada PT. Semen Bosowa Maros) - Harjauri Ma’rifat; Saiful Muchlis; Raodahtul Jannah (Universitas Islam Negeri Alauddin Makassar, 2022)
The purpose of this study was to find out how the understanding or meaning of PT. Semen Bosowa Maros regarding environmental accounting, and how the implementation of environmental accounting by PT. Semen Bosowa Maros in determining the environmental costs incurred. This research is a qualitative research using a phenomenological approach. The results of this study indicate that environmental accounting is interpreted as a form of social and environmental care carried out by the company and as a form of responsibility for all company operational activities that have an impact on the surrounding environment. The application of environmental accounting is also expected to be one of the supports for the survival of the company. From this study it is also known that the company applies environmental accounting following the regulations set by the government, so that the application of environmental accounting becomes a company obligation in accordance with existing rules. The costs of environmental management become the company's liability in each period, so these costs are reported in the income statement as part of the company's operating costs.